The impact of foreign direct investment (FDI) on the sustainable economic development - Sahar Kareem Gatea3Nadia Khutheir Ganawi, Amel Asmar Zaboon (Opción, 2020)
China has become an economic giant in the world due to its mega, advanced and innovative economic policies. This research covers the same thing, which describes the impact of Foreign Direct Investment (FDI) on the sustainable economic development in China. We compare Chinese data with other developed and developing countries, and then we come to know that FDI proves itself a force in the economic growth of China most importantly in industrialization field. Considerable and helpful results are found for the connection of FDI with economic growth in China, and also for the sustainability of the relation.